Gardenoside Hinders Caspase-1-Mediated Hepatocyte Pyroptosis Through the CTCF/DPP4 Signaling Pathway - Shen, Tian; Lei, Tao; Chen, Lin; Zhu, Bing-Bing; Xu, Bi-Lin; Zhang, Cui-Ping; Wang, Hong-Ping (Frontiers in Physiology, 2021)
Non-alcoholic fatty liver disease (NAFLD) is accompanied by a typical inflammatory damage and cell death. As a pro-inflammatory form of cell death, pyroptosis participates in important pathological processes involved in NAFLD. Regulatory roles of both CCCTC-binding factor (CTCF) and dipeptidyl peptidase 4 (DPP4) have reported in NAFLD, but it is still unclear whether the mechanism of action of gardenoside, a potential therapeutics for NAFLD, can be driven via these proteins. In this study, the direct interaction between CTCF and DPP4 was first confirmed by a dual-luciferase reporter assay system. Then, a cell model of NAFLD was established by induction with palmitic acid (PA) and lipopolysaccharide (LPS). A mouse NAFLD model established. The effect of gardenoside on both the cell and mouse models of NAFLD was aslso investigated. Increased lipid accumulation, NLRP3 inflammasome activation, and hepatocyte pyroptosis were recorded in NAFLD in vitro and in vivo. Gardenoside treatment effectively reduced the lipid accumulation , increased cell viability, reduced ROS generation and attenuated pyroptosis and apoptosis in NAFLD in vitro and in vivo models. Alterations in these biological processes were evidenced by the decreased expression levels of several pro-pyroptotic markers including NLR family, pyrin domain-containing 3 (NLRP3), apoptosis-related speckle-like protein (ASC), caspase-1 p20, Gasdermin D N-terminal domain (GSDMD-N) and IL-1β, along with simultaneously decreased CTCF and DPP4 levels. Importantly, CTCF silencing or DPP4 silencing exhibited effects similar to gardenoside treatment while CTCF overexpression counteracted this trend, which indicated that CTCF might be a target responsible for gardenoside-induced alleviation of NAFLD, such therapeutic effects might be achieved through controling the expression of the direct target of CTCF (DPP4) and several down-stream molecules. In general, the current study provides a promising strategy for NAFLD treatment.